Indium phosphide ICs unleash the high-frequency spectrum. - Raghavan, G.
As demand for high-frequency communications mushrooms, indium phosphide technology has emerged as a leading candidate for chips to meet that need. Already InP ICs with thousands of transistors are reaching speeds of over 65 GHz. The necessary level of complexity and speed is available from HBT ICs built on indium phosphide substrates using materials with different energy bandgaps for the emitter, the base, and, sometimes, the collector. They are the only viable option today for ICs that require 30GHz-plus frequencies and LSI complexity. Applications that can get by with lower levels of integration but require higher frequency operation of 94 GHz and beyond, such as missile radar, are currently best served by indium phosphide high-electron-mobility transistors (HEMTs)
Keywords: 10 to 100 GHz; HBT ICs; InP; LSI complexity; Energy bandgaps; High-electron-mobility transistors; High-frequency communications